DEVELOPMENT OF AUDITORY PERCEPTION IN CHILDREN WITH VISUAL IMPAIRMENTS - Sulaymanova Muhlisa Kozimjon qizi; Umida Mexmanovna Utbasarova (Web of Journals Publishing, 2025)
This article highlights the methodological foundations and practical methods for developing auditory perception in children with visual impairments. It analyzes the possibilities of using auditory analyzers as a compensatory tool for blind and visually impaired children, the role of hearing in perceiving the environment, and effective systems of special correctional activities.
Keywords: Visual impairment, auditory perception, sensory compensation, correctional activities, acoustic perception, blind children, visually impaired children.